Designing a Network Using Network Intrusion Detection System (NIDS) for Detecting Attacks on the Server in the Computers Laboratory at Suryakancana University - Mohamad Kany Legiawan; Muhamad Rifki Arisagas (JURNAL SISFOTEK GLOBAL, 2023)
The escalating reliance on technology and network systems has given rise to mounting concerns regarding digital asset security. This journal presents the design and implementation of a Network Intrusion Detection System (NIDS) intended to detect potential attacks on servers within the Computers Laboratory at Suryakancana University. The research follows the Network Development Life Cycle (NDLC) methodology, encompassing phases from analysis to simulation prototyping. Despite successful implementation challenges were encountered due to server maintenance issues and continuous updates, leading to a partial implementation of NIDS using the Snort tool. The journal provides insights into the significance of cybersecurity in educational environments and underscores the importance of vigilant network security measures